Rancang Bangun Automatic Smart Energy Meter Berbasis RFId - Muhammad Fahmi Hakim; Imron Ridzki; Ichwan Bayu Kusuma (Politeknik Negeri Malang, 2021)
The development of technology today makes it easier for humans in their daily activities. One of them is in the digital world. In the industrial era 4.0. more and more companies are issuing breakthrough new products based on digital technology that aim to be practical in their use. One of the technologies applied is the use of smart cards. For example in the use of smart keys in homes and car doors. Then in the current transaction process, many have implemented this smart card technology. The purpose of this research is to apply the latest technology in the energy transaction process which will be applied to the KWh meter. The smart card used is RFId and is integrated in the database and website so that its use is more practical and flexible. Then the use of this smart card can be applied to the smart energy meter so that later the prepaid energy transaction process can be applied easily with this smart energy meter.